Moral Emotions in the Latin-America: A Socio-cultural and Socioeconomic Analysis - Londoño-Cortés, María A.; Idárraga-López, Maria Camila; Mercadillo, Roberto E.; Cudris-Torres, Lorena; Javela, Jose Julian (Current Psychiatry Research and Reviews, 2023)
Background: Understanding how people respond to societal problems requires analyzing the experience and expression of moral emotions (ME). Despite the fact that various research on moral emotions have been conducted in Latin America, this analysis has yet to be completed, despite the fact that it is particularly important due to its link to violence and inequality. Methods: The goal of this paper is to evaluate ME research in Latin America and discuss it within the context of a socio-cultural and socio-economic analysis of this region of the world. The PRISMA searching method was applied in Scopus, PubMed, ScienceDirect, Scielo, and Redalyc databases. Results: The findings revealed 58 publications in Latin America that dealt with moral feelings and were consequently studied. Colombia, Mexico, Brazil, and Chile are the countries that have tackled the issue the most. Compassion, devotion, and gratitude were the three most explored MS and associated themes. Conclusion: The impact of moral emotions on persons living in various Latin American environments, as well as their prosocial acts aimed at combating violence and inequality, is revealed.
Keywords: inequality